2008
DOI: 10.1590/s0004-27492008000500002
|View full text |Cite
|
Sign up to set email alerts
|

Endoftalmites bacterianas com culturas positivas: uma revisão de 6 anos

Abstract: de sensibilidade à oxacilina, 89,61% à ciprofloxacina e 100% à gatifloxacina e moxifloxacina. A forma de aquisição predominante foi a pós-operatória (60,65%). Conclusão: Observamos baixa sensibilidade da cultura para o diagnóstico etiológico das endoftalmites. Uma terapia antimicrobiana ou profilaxia empírica deve ser ativa contra os microrganismos gram-positivos, particularmente contra estafilococos. Estudos de vigilância de resistência bacteriana são importantes para adequação desses esquemas. RESUMO INTRODU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 36 publications
0
4
0
3
Order By: Relevance
“…In clinical cases suspected of endophthalmitis, cultures show a positivity of about 25% to 56% (11)(12)(13)(14)(15) . The low sensitivity of microbiological culture is due to various factors such as small quantity of specimen, fixation of microorganisms in solid surfaces (intraocular lens, lens fragments, capsule) and consequent decrease of cells in the vitreous/aqueous humor, use of antibiotics before the collection of clinical material and the presence of fastidious microorganisms such as agents causing endophthalmitis (14) .…”
Section: The Need For Pcr In Ophthalmologymentioning
confidence: 99%
“…In clinical cases suspected of endophthalmitis, cultures show a positivity of about 25% to 56% (11)(12)(13)(14)(15) . The low sensitivity of microbiological culture is due to various factors such as small quantity of specimen, fixation of microorganisms in solid surfaces (intraocular lens, lens fragments, capsule) and consequent decrease of cells in the vitreous/aqueous humor, use of antibiotics before the collection of clinical material and the presence of fastidious microorganisms such as agents causing endophthalmitis (14) .…”
Section: The Need For Pcr In Ophthalmologymentioning
confidence: 99%
“…Los estudios microbiológicos convencionales para el diagnóstico de las endoftalmitis mediante cultivo de humor vítreo, humor acuoso y coloración de Gram, tienen el gran inconveniente de presentar baja sensibilidad. Según los diversos estudios, los cultivos muestran una positividad variable, entre 24% a 56% de los casos sospechosos (16,(22)(23)(24) . En el presente trabajo un 23,5% de las muestras analizadas resultaron ser positivas por el método convencional.…”
Section: Discussionunclassified
“…The sensitivity of culture after diagnostic vitrectomy for the diagnosis of chronic infectious uveitis has been reported between 16.7 to 96% 3, 9, 10, 27 with higher sensitivity reported in case series were there was a high pre-test probability for chronic endogenous or post-operative endophthalmitis. 9 For acute post-operative endophthalmitis, data from the Endophthalmitis Vitrectomy Study showed a yield of 66% for culture and 41% for gram stain for patients undergoing vitrectomy.…”
Section: Special Considerations Based On Infectious Etiologymentioning
confidence: 94%